0156 In the front stalls: Auditions, rehearsals and team training. (2nd November 2015) - Ivermee, Clare; Liotiri, Despoina; Snelgrove, Huon; Broom, Christopher; Gosling, Nick; Ayres, Benjamin; Hammond, Sarah; McAnulty, Greg
Abstract : Background: Simulation has traditionally been used as an educational method embedded in well-structured curricula. Separate medical and allied health professional curricula have embraced the evidence-based value of simulation-based education in improving patient safety. 1 Although multidisciplinary teamwork is at the heart of the high priority safety agenda of modern healthcare systems, 2 little work has been done so far on effectively identifying the needs of teams working together in order to create integrated healthcare team training curricula. 3 Methodology: We developed a mobile, simulation-based team-training programme for anaesthetic, surgical and nursing staff in theatres and recovery using a Participatory Action Research (PAR) approach. 4 A needs analysis was performed, which included literature searches, meetings and focus groups with stakeholders. Initial pilot simulation sessions were done to identify context specific issues and the potential role of simulation-based training. Following this, iterative cycles of observation, evaluation and action planning were conducted to develop a model of practice-based learning in theatres. Results: Eighty theatre staff were engaged in the development of the multiprofessional team training programme. Collated action plans from bimonthly in situ theatre simulations led to a dynamic training needs and evaluation model. These highlighted medical management, non-technical skills and system factors. Observation tools and safety questionnaires were deployed with staff to develop dialogue across professional roles about safety and led to greater confidence in briefing and debriefing. Potential impact: Theatre staff developed skills and tools for ownership of their own training priorities, encouraging more sustainable, long-term educational programmes. We learned that the development of a simulation-based training programme in an essentially unstructured experiential learning context is complex, requiring a high degree of local system sensitivity and organisational pragmatism. References: Gaba DM. The future vision of simulation in health care. Qual Saf Health Care 2004;13:i2–i10 Sevdalis N, Hull L, Birnbach DJ. Improving patient safety in the operating theatre and perioperative care: obstacles, interventions and priorities for accelerating the process. BJA 2012;109:i3-i16 Cumin D, Boyd MJ, Webster CS, Weller JM. A systematic review of simulation for multidisciplinary team training in operating rooms. Simul Healthc 2013;8:171–9 Coghlan D, Brannick T. Doing action research in your organisation . Sage: London, 2014